Cooling of floating photovoltaics and the importance of water temperature. (April 2021) - Kjeldstad, Torunn; Lindholm, Dag; Marstein, Erik; Selj, Josefine
Highlights: Direct comparison between air-cooled string and water-cooled string. Thermal contact with water increases yield with 5–6%. Thermal model derived to include both air and water temperature. Performance data and thermal model predict U-value of 70–80 W/m 2 K for membrane FPV. For membrane based FPV systems, water temp needed when estimating module temp. Abstract: Enhanced performance of floating PV due to water cooling is widely claimed, but poorly quantified and documented in the scientific literature. In this work, we assess the effect of water cooling for a specific technology developed by Ocean Sun AS, consisting of a floating membrane with horizontally mounted PV modules allowing for thermal contact between the modules and the water. The impact of thermal contact with water on energy yield is quantified using production data from a well-instrumented 6.48 kW installation at Skaftå, Norway. In addition, we apply a thermal model that incorporates the effect of heat transport from the module to the water to estimate the module temperature. By comparing a module string in thermal contact with water with a module string with an air gap between the water and the modules, we find that the water-cooled string had on average 5–6% higher yield compared to the air-cooled string. Also, we find that the system in thermal contact with water has a U-value of approximately 70–80 W/m 2 K, and that it is necessary to consider the water temperature for a more accurate calculation of the module temperature.